Evaluation of the Rock Uplift Pattern in the Central Yunnan Subblock, SE Tibetan Plateau: Based on the Bedrock Channel Profile - Yu, Liang; Dong, Youpu; Zhou, Weiwei; Zhang, Dongyue; Wang, Dan; Yu, Huayu; Ren, Yangyang; Li, Jiangtao (Frontiers in Earth Science, 2022)
The uplift pattern of the southeastern Tibetan Plateau is strongly related to the topographic evolution stemming from the India–Eurasia collision. However, whether strain is localized along major faults that bound large tectonic blocks or is accommodated across regions has been strongly debated. In this study, we used stream power incision models to obtain the distribution pattern of the channel steepness indices to understand the rock uplift pattern across the area, as increased channel steepness indices often correlate with the rock uplift rates. In this study, the river longitudinal profiles were analyzed to obtain the distribution of the channel steepness indices in the Central Yunnan subblock. The results suggested very weak correlations between the steepness indices and the lithology, precipitation, sediment flux, or channel concavity indices. Along the Xiaojiang strike–slip fault and the interior subblock, the uplift rate was slower, while the northern part had uplifted faster and was controlled by thrust fault systems. The channel steepness increased gradually from south to north. Thus, the distribution pattern of the normalized channel steepness, ksn, index within the Central Yunnan subblock provides notable support for the argument for the thrusting transformation-limited extrusion model of the Tibetan Plateau.